(untitled) (Global Journal of Computer Science and Technology, 2022)
This paper discusses the idea and the design of an automated system for storage and management of mycotoxins reports for decision making Mycotoxins are poisonous chemical compounds produced by certain fungi Mycotoxins are fungal secondary metabolites that contaminate various feedstuffs and agricultural crops The contamination of food by mycotoxins can occur before production during storage processing transportation or marketing of the food products High temperature moisture content and water activity are among the factors that facilitate the production of mycotoxins in food The five major mycotoxins produced in food and feedstuffs are Aflatoxins ochratoxins fumonisins deoxynivalenol and zearalenone